MDM4 SNP34091 (rs4245739) and its effect on breast‐, colon‐, lung‐, and prostate cancer risk. (16th October 2015) - Gansmo, Liv B.; Romundstad, Pål; Birkeland, Einar; Hveem, Kristian; Vatten, Lars; Knappskog, Stian; Lønning, Per Eystein
Abstract : The MDM4 and the MDM2 protein are major inhibitors of the tumor suppressor p53. Polymorphisms in both genes may affect cancer risk. In this large population‐based case–control study, we assessed the potential association between MDM4 SNP34091 and the risk for breast‐, colon‐, lung‐, and prostate cancer, alone and in combination with MDM2 SNP309. We found that the MDM4 SNP34091C is associated with reduced breast cancer risk, particularly among individuals carrying the MDM2 SNP309GG genotype. Abstract: The MDM4 protein plays an important part in the negative regulation of the tumor suppressor p53 through its interaction with MDM2. In line with this, MDM4 amplification has been observed in several tumor forms. A polymorphism (rs4245739 A>C; SNP34091) in the MDM4 3′ untranslated region has been reported to create a target site for hsa‐miR‐191, resulting in decreased MDM4 mRNA levels. In this population‐based case–control study, we examined the potential association between MDM4 SNP34091, alone and in combination with the MDM2 SNP309T>G (rs2279744), and the risk of breast‐, colon‐, lung‐, and prostate cancer in Norway. SNP34091 was genotyped in 7, 079 cancer patients as well as in 3, 747 gender‐ and age‐matched healthy controls. MDM4 SNP34091C was not associated with risk for any of the tumor forms examined, except for a marginally significant association with reduced risk for breast cancer in a recessive model (OR = 0.77: 95% CI = 0.59–0.99). Stratifying according to MDM2 SNP309 status, we observed a reduced risk for breast cancer related to MDM4 SNP34091CC among individuals harboring the MDM2 SNP309GG genotype (OR = 0.41; 95% CI = 0.21–0.82). We conclude, MDM4 SNP34091 status to be associated with reduced risk of breast cancer, in particular in individuals carrying the MDM2 SNP309GG genotype, but not to be associated with either lung‐, colon‐ or prostate cancer.